FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN PADA PEMERINTAH PROVINSI DI PULAU SUMATERA - Anggraini, Mita Dwi; Sari, Kartika Rachma; Armaini, Rosy (Universitas Muhammadiyah Palembang, 2024)
This research was conducted in order to achieve the goal of understanding the Factors Affecting Budget Absorption in the Provincial Government on the Island of Sumatra. The data utilized is data that is already available in the Audit Report sourced through the BPK RI website and Regional Regulations on the BPKAD website in provinces on the island of Sumatra. The population that is the focus of this research includes all provinces on the island of Sumatra with a total of 10 provinces on the island of Sumatra for the 2018-2022 fiscal year and the sampling method used is a comprehensive sampling method or saturated sampling with an observation unit of 50 samples. Data processing involves assistance in the form of the Eviews version 12 application. The results of this study indicate that partially Fiscal Stress does not affect Budget Absorption while Budget Setting Time partially affects Budget Absorption. Simultaneously Fiscal Stress and Budget Setting Time affect Budget Absorption